Experimental study of water vaporization occurring inside a channel of a smooth plate-type heat exchanger at subatmospheric pressure. (5th August 2016) - Giraud, Florine; Toublanc, Cyril; Rullière, Romuald; Bonjour, Jocelyn; Clausse, Marc
Highlights: Experimental set-up working as a pump-assisted closed-loop thermosyphon was built. Water vaporization inside a channel of a plate-type heat exchanger at subatmospheric pressure was observed. Three main flow regimes were identified. Influence of these regimes on heat transfer were discussed. Overall heat transfer coefficients were estimated. Abstract: In order to be able to design properly low-pressure evaporators for sorption chillers, expertise on vaporization of the refrigerant under conditions that might occur in these evaporators is fundamental. However, few studies focus on this subject and there is a lack of knowledge about vaporization (boiling or evaporation) phenomena occurring in compact evaporators at low pressure. The objective of this article is thus to go further in the understanding of phenomena occurring in compact plate-type evaporators. In that goal, an experimental test setup was designed and built. It allows the observation of the water vaporization in a channel mimicking that of a plate heat exchanger of standard dimension (0.2 m width × 0.5 m height) under various operating conditions (working pressure ranging from 0.85 kPa to 16 kPa, secondary fluid temperature ranging from 10.9 °C to 23.1 °C, filling ratio ranging from 1/2 to 1/10 of the whole channel height). During these experiments, three main flow regimes were observed and three different working areas were identified: a pool boiling area, a vapor area, and a film evaporation area. In the latter, the creation of a liquid film due to the splashing of droplets is observed. These droplets result from the break-up of the membrane of a previously formed large bubble. The bubble formed is of several centimeters in diameter and appears in the pool boiling area, few centimeters below the free surface. It was shown that the major part of the cooling capacity is achieved in the film evaporation area. As a matter of fact, it is possible to predict the overall cooling capacity obtained experimentally with a maximum relative difference of 30% directly from the evaluation of the overall heat transfer coefficients in that area.